MODEL PENGEMBANGAN PERPUSTAKAANN PGSD FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA UNTUK MEMBUDAYAKAN MINAT BACA MAHASISWA - Sudrajat, Ajat (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2014)
Development of reading includes four kinds of activities, namely planning program growth and development of reading, and organize the implementation of the program, control the execution of the program and assess the implementation of the program of growth and development of reading interest, both within the family, school and community. Library can be used as a source of learning for the students because FIP PGSD library UNJ not only have a collection of books, but also in the form of a device for the presentation of the material through the CD, VCD, CD-ROMs, and the Internet. Library is an effective learning resources to increase knowledge. Availability of library materials allow each student select them according to interest and importance. The more students who diligently read also increase the level of knowledge. In addition to functioning as a place to get information, the library also serves PGSD FIP UNJ for education, learning and research. Therefore, the distribution of the collections of information should be directed to the learning needs of students.